The Psychological reversal and Boundaries in the Mind and their relationship Humility - Intellectual arrogance among postgraduate students - Noora Kream Salih Al- Hashimi; Dr. Rasheed Nassir khelifeh (Journal of College of Education, 2025)
The current research aims to identify: 1- Mental limits for postgraduate students To achieve the objectives of the research, the researcher relied on the psychological limits scale of Abbas 2012 prepared on Hartmann’s theory, as the number of its final paragraphs reached 48 paragraphs, after verifying the psychometric measurement. And she applied it to the research sample, which numbered (226) graduate students in 12 faculties of the University of Wasit, for the master’s and doctoral levels for the academic year (2022-2023), and they were chosen randomly and proportionally. After processing the data statistically, the current research reached the following results: - Graduate students have thin personal boundaries